Strengthening Customary Village Law and Transcendental Communication in the Terunyan Burial Tradition: A Community Engagement Approach in Bali - Ani Purwati; Gita Ruslita; Aris Yulia; Siti Chariyah Batubara; Euis Herlina Mujaswati (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The mepasah burial tradition practiced by the Bali Aga community in Terunyan Village, Bali, represents a distinctive form of local wisdom in treating the deceased through open-air placement without burial or cremation. This tradition is grounded in customary village law (awig-awig) and sustained through transcendental communication that constructs symbolic relationships between humans, ancestors, nature, and the local cosmological order. In contemporary social developments, the continuity of the mepasah tradition faces increasingly complex socio-legal challenges, including the declining internalization of awig-awig values among younger generations, the emergence of social friction due to differing interpretations of customary norms, and unequal relations between indigenous communities and external actors, particularly the tourism sector and state institutions. These challenges are exacerbated by the limited operationalization of formal recognition of customary village law within public policy practices, resulting in the marginalization of customary norms when confronted with positivist-oriented health and environmental regulations. This Community Engagement Program (Pengabdian kepada Masyarakat/PKM) focuses on strengthening the customary law of Terunyan Village by positioning transcendental communication as a source of normative and cultural legitimacy in the implementation of burial traditions. The program employs a participatory socio-legal approach through the review of awig-awig, participant observation, focus group discussions (FGDs), and in-depth interviews with customary leaders and community members, in line with the constitutional recognition of indigenous communities under Article 18B paragraph (2) of the 1945 Constitution of the Republic of Indonesia and the recognition of customary villages under Law Number 6 of 2014 on Villages. The novelty of this program lies in the design of a customary law strengthening model that integrates transcendental communication as a mediating mechanism between customary norms, the state legal framework, and external tourism pressures. The implementation results demonstrate increased collective legal awareness, strengthened social legitimacy of customary village law, and the formation of transcendental communication patterns that function as mechanisms for social conflict resolution and strategies for customary preservation. These findings affirm that the sustainability of local traditions in Bali requires a harmonious integration of customary law, community social dynamics, and transcendental communication as the foundation of equitable customary village governance.